Multiplicity and ‘The International’ as Critique – A Forum (2023)
This forum reconsiders the standing of ‘the international’ in relation to ‘critique’. Is this relation best understood in ways reminiscent of the ‘Fourth Great Debate’, where the international, associated with political realism, was targeted for deconstruction by critical approaches drawn from outside International Relations? Or is the international, on the contrary, itself a source of potential critique needing to be excavated and utilized, as recent debates on ‘societal multiplicity’ and Uneven and Combined Development have suggested? In this forum, seven international theorists debate the latter question from a range of intellectual perspectives..